MALAYSIAN LEGAL SOURCES: PRINT - N. N., Edzan (Malaysian Journal of Library and Information Science, 2000)
Identifies and provides a brief description of the various print form of Malaysian legal sources which are available in the 1990’s. Malayan Law Journal has been identified as the most prolific legal publisher in Malaysia It is suggesed that the various Government bodies should actively publish since they are the sole producer of legal information.